Analysis of Polar Precursors of 1, 3, 5, 7‐Tetranitro‐1, 3, 5, 7‐tetrazocine (HMX) Using Hydrophilic Interaction Chromatography. Issue 1 (13th October 2014) - Zhu, Chao; Meng, Zihui; Xu, Zhibin; Xue, Min; Wang, Fengyan; Liu, Yue; Lin, Zhihui; Qin, Guangmin; Ge, Zhongxue; Wang, Bozhou
Abstract Octahydro‐1, 3, 5, 7‐tetranitro‐1, 3, 5, 7‐tetrazocine (HMX) is currently one of the most widely used explosives. 1, 3, 5, 7‐Tetraacetyl‐1, 3, 5, 7‐tetraazacyclooctane (TAT) is an attractive precursor for the synthesis of HMX; the nitration of this key precursor results in both high yield and purity under mild condition. TAT can be prepared either by acetylation of 2, 6‐diacetyl‐pentamethylenetetramine (DAPT) or by the condensation of ACN and 1, 3, 5‐trioxane. However, TAT and DAPT are polar compounds, and are difficult to analyze using reverse phase liquid chromatography. Herein, a chromatography method for the direct separation of these polar compounds was developed using hydrophilic interaction chromatography (HILIC) using a Venusil HILIC column, with ACN/water (95/5, v/v) as the mobile phase. The chromatographic analysis and identification of these polar compounds provide valuable information for the optimization of the synthetic process of TAT.